Gỉai bài toán này:
(1-1/5)x(1-2/5)x(3/5)x....x(1-2005/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/ (2x+3)(x-4)+(x+5)(x-2)=(3x-5)(x-4)
<=> 2x2 - 8x + 3x - 12 + x2 - 2x + 5x - 10 - 3x2 + 12x + 5x - 20 = 0
<=> 15x - 20 = 0
<=> 15x = 20
<=> x = 4/3
\(\frac{1}{1\cdot3}+\frac{1}{3\cdot5}+\frac{1}{5\cdot7}+...+\frac{1}{x\cdot\left(x+2\right)}=\frac{20}{41}\)
\(\frac{1}{2}\cdot\left(\frac{2}{1\cdot3}+\frac{2}{3\cdot5}+\frac{2}{5\cdot7}+...+\frac{2}{x\cdot\left(x+2\right)}\right)=\frac{20}{41}\)
\(1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{x}-\frac{1}{x+2}=\frac{20}{41}:\frac{1}{2}\)
\(1-\frac{1}{x+2}=\frac{40}{41}\)
\(\frac{1}{x+2}=1-\frac{40}{41}\)
\(\frac{1}{x+2}=\frac{1}{41}\)
\(\Rightarrow x+2=41\Rightarrow x=39\)
A = ( 1 - \(\dfrac{1}{5}\)).(1 - \(\dfrac{2}{5}\)).(1 - \(\dfrac{3}{5}\))...(1 - \(\dfrac{2005}{5}\))
A = (1- \(\dfrac{1}{5}\)).(1 - \(\dfrac{2}{5}\)).(1-\(\dfrac{3}{5}\)).(1 - \(\dfrac{4}{5}\)).(1 - \(\dfrac{5}{5}\))....(1 - \(\dfrac{2005}{5}\))
A = (1 - \(\dfrac{1}{5}\)).(1- \(\dfrac{2}{5}\)).(1- \(\dfrac{3}{5}\)).(1- \(\dfrac{4}{5}\)).(1-1)....(1- \(\dfrac{2005}{5}\))
A = (1- \(\dfrac{1}{5}\)).....0...(1- \(\dfrac{2005}{5}\))
A =0